In vitro and in vivo antiviral effect of Fufang Yinhua Jiedu granules (FFYH) combined with oseltamivir against influenza A virus - Zhihui Zheng; Yuqian Zhang; Ming Li; Wenlei Wang; Hailin Wei; Qin Su; Ronghua Wang; Weiqing Shi; Lei Wang; Jianxiong Wu; Shuheng He; Xiaoquan Wang; et al. (Elsevier, 2023)
Introduction: Our recent work demonstrated that Fufang Yinhua Jiedu granule (FFYH) exhibited a good antiviral activity against influenza A virus (IAV). However, whether the combinations of FFYH with antiviral agents show synergistic action against IAV remains unclear. Methods: In vitro combinations of FFYH and oseltamivir against IAV were evaluated using Madin-Darby canine kidney (MDCK) cell model. In vivo combinations effect against IAV (H1N1, A/FM1/1/33) was performed using Institute of Cancer Research (ICR) mice model. The potential mechanism of FFYH against IAV in vitro and in vivo was investigated by RT-PCR or Western blot. Results: In vitro combinations of FFYH and oseltamivir could synergistically inhibit the replication of IAV and prevent the cell pathogenic effect (CPE) caused by IAV. In in vivo assays, FFYH combined with oseltamivir not only could markedly improve the sick signs, food intake, weight loss, hematology parameters, inflammatory factors and lung pathological changes, but also significantly increased the survival rate and the survival time of the IAV-infected mice. In addition, virus titers in lung tissue and lung index were markedly reduced on day 6 post-infection by combination therapy of oseltamivir combined with FFYH at 0.25 and 0.5 g/kg/d. The studies of mechanism of action indicated that the combination effect of FFYH with oseltamivir against IAV might be achieved through regulating TLR7-MyD88 signaling pathway. Conclusions: The combinations of FFYH and oseltamivir not only exhibited in vitro synergistic antiviral activity on IAV, but also showed better protective effect against lethal IAV infections than oseltamivir or FFYH each on its own. These findings might provide a new option for the treatment of IAV infection in the future.